No Work No Food: An Interpretive Analysis of Paul’s Admonition in 2 Thessalonians 3: 6-13 in the Context of the Discourse on Religion and Poverty - Adelakun, Adewale J.; Ajadi, Oluseye E. (European Scientific Journal, ESJ, 2020)
Linking religion to poverty is not uncommon in the postmodern world. Religious crises, no doubt, are one of the major causes of indescribable suffering and untold hardship in many countries. Ironically, religious people have also been noticed to be happy in the face of poverty, especially, when it is necessitated by their religiosity. For this reason, Marxist philosophy is antagonistic to religion. Marxism argues that religion impoverishes people through its promise of a better place for believers who endure hardship on earth. Religion, Marxists argue, has been used to protect the oppressors while consoling the oppressed. In this regard, religion is described as the opium of the people. This paper agrees with the view that religion can be a spur for poverty. On the other hand, religion can serve as a catalyst for economic development. The second letter of Paul to the Thessalonians 3: 6-13 is interpreted to substantiate these propositions. The paper adopts historicalgrammatical method to interpret the text. The paper points out that some Christians in Thessalonica misunderstood Paul’s teaching about the imminence of the parousia, (that is, second coming of Jesus Christ). Consequently, they abandoned their work while waiting for Jesus to come. This compelled Paul to advocate No-Work-No-Food rule. The submission of this paper is that religious role in human development is ambiguous, depending on how religious adherents understand the teachings of their religions.